A new species of Epidendrum (Orchidaceae) from The Central Andes of Antioquia, Colombia - Rincón-González, Milton; Santiago Ayala, Elizabeth; Hágsater, Eric (Lankesteriana: International Journal on Orchidology, 2022)
The new species, Epidendrum sonsonense, was discovered while determining the herbarium specimens housed in the herbarium of Fundación Jardín Botánico Joaquin Antonio Uribe, JAUM. The species belongs to the informal Macrostachyum group and is endemic to the Paramo of Sonsón, Department of Antioquia, Colombia, characterized by the thickened stems, densely many-flowered raceme, and creamy-yellow flowers. A Lankester Composite Digital Plate (LCDP) of fresh material collected at the type locality is presented here. Studying additional collections at Colombian herbaria produced additional specimens of the same species.